1984
DOI: 10.1177/027112148400400307
|View full text |Cite
|
Sign up to set email alerts
|

Classroom-based Social Skills Instruction for Severely Handicapped Preschool Children

Abstract: Social skills instruction has been a neglected aspect of educational programs for young severely handicapped children. This paper offers suggestions, drawn from a variety of research literatures, for building classroom-based social skills instructional programs. Important features of classroom programming included allotting a specific portion of the class schedule but also providing opportunities for generalization across the day. The differential effectiveness of play activities and materials for supporting s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…How ever, teachermediated intervention strategies may be needed in generalization conditions to continue to encourage inter actions between preschoolers with disabilities and their typically developing peers. Strategies such as teacher arrangement of children with disabilities into groups that contain more socially skilled children (Guralnick & Groom, 1988;Odom & Strain, 1984), teacher prompting and prais ing (McConnell, Sisson, Cort, & Strain, 1991), and group contingencies on the social interactions of an inclusive group of children (Lefebvre & Strain, 1989) would be appropriate techniques provided that the teacher does not attempt to direct the children's play, as this has been found to hamper peertopeer interaction with typically develop ing children (Carta, Sainato, & Greenwood, 1988). It may be unreasonable to assume that preschoolers with disabili ties should be able to generalize newly learned skills to an untrained classroom context without teacher assistance.…”
Section: Discussionmentioning
confidence: 99%
“…How ever, teachermediated intervention strategies may be needed in generalization conditions to continue to encourage inter actions between preschoolers with disabilities and their typically developing peers. Strategies such as teacher arrangement of children with disabilities into groups that contain more socially skilled children (Guralnick & Groom, 1988;Odom & Strain, 1984), teacher prompting and prais ing (McConnell, Sisson, Cort, & Strain, 1991), and group contingencies on the social interactions of an inclusive group of children (Lefebvre & Strain, 1989) would be appropriate techniques provided that the teacher does not attempt to direct the children's play, as this has been found to hamper peertopeer interaction with typically develop ing children (Carta, Sainato, & Greenwood, 1988). It may be unreasonable to assume that preschoolers with disabili ties should be able to generalize newly learned skills to an untrained classroom context without teacher assistance.…”
Section: Discussionmentioning
confidence: 99%
“…There has been considerable attention in the professional literature to procedures that promote the social competence of children with disabilities in integrated preschool settings (e.g., Guralnick, 1990;Odom & McEvoy, 1988;Odom & Strain, 1984a). Several studies have found that placement of these children in regular preschools is not sufficient to produce improvements in their social behaviors (Beckman, 1983;Beckman & Kohl, 1984;Guralnick, 1981;Honig&McCarron, 1988;Ipsa, 1981;Odom & McEvoy, 1988;White, 1980).…”
Section: Training Supervisors In a Collaborative Team Approach To Promentioning
confidence: 99%
“…The manual emphasized the importance of the collaboration of resource and classroom teachers on the development of a plan for the entire class. Areas of curriculum and activities, teacher instructional behaviors, and physical arrangements were selected for their correspondence to the three classroom variables identified by Odom and Strain (1984a) The supervisor was instructed to give feedback to teachers without specific direction or correction.…”
Section: Experimental Designmentioning
confidence: 99%
“…These include (a) the presence of naturally occurring distractions in inclusive classrooms (Charlop & Walsh, 1986;McGee et al, 1992); (b) the personal characteristics of the peers including their age and social and communicative competence (Carter & Maxwell, 1998); (c) the extent to which peers and children with autism become reliant on teacher prompts (Goldstein et al, 1992;McGee et al, 1992); (d) the effects of fatigue associated with studies conducted over a long period of time (Odom & Strain, 1984a); and (f) the characteristics of the children with autism, including the presence of selfstimulatory behaviours (Strain & Kohler, 1998), their social and communication skills (Strain & Kohler, 1998), and their responsiveness to peers (Charlop & Walsh, 1986). Carter and Maxwell (1998) noted that children without disability are less likely to persist in interactions with children with autism who are not responsive.…”
mentioning
confidence: 99%